Review an assessment of electromagnetic wave propagation in sand and dust storms at microwave and millimeter wave band - part II - Abdulwaheed, Musa; Saad Osman, Bashir; Hassan Abdalla Hashim, Aisha (EMW Publishing, 2014)
Suspended particles in the atmosphere during sand and dust storms have numerous consequences on electromagnetic wave propagation in arid regions. The electromagnetic wave signal may suffer attenuation and cross polarization upon encounter with the suspended particles. However, meager information has hitherto been reported about effect of storms on the telecommunication systems operating in such regions. This paper presents a survey of current understanding of the electromagnetic wave propagation in sand and dust storms. A review of the literature covering electromagnetic scattering theory and applications is given. The review describes the principle of approach and technology adopted for the investigation highlighting both strengths and drawbacks. Detailed parametric assessment of the effects of storms on wave propagation as it concerns signal attenuation and cross polarization is also carried out. The results demonstrate that most authors have calculated the attenuation effect, revealing that it is not very significant unless very high suspended dust densities are assumed (i.e., during severe sand and dust storms). A few papers indicate the possibility of more significant cross polarisation. The obvious gap in knowledge of this field is finally also clearly established.